Clinical characteristics and comorbidities associated with testosterone prescribing in men. (24th November 2021) - Sharma, Aditi; Ul‐Haq, Zia; Sindi, Emad; Al‐Sharefi, Ahmed; Kamalati, Tahereh; Dhillo, Waljit S.; Minhas, Suks; Jayasena, Channa N.
Abstract: Objective: Testosterone replacement therapy (TRT) is recommended for the treatment of symptomatic hypogonadism in men. Data on prescription behaviours are, however, limited and conflicting. The objective of this study was to investigate clinical characteristics associated with the likelihood of being prescribed TRT by general practitioners (GP) in North‐West London (NWL). Design: Retrospective cohort study using Discover database of GP‐registered patients in NWL between 2015 and 2019. Patients: We identified 20, 299 men aged ≥18 years with serum total testosterone measurement (TT) and without prior TRT prescription records. Measurements: We determined whether TRT was subsequently commenced, while analysing clinical characteristics related to hypogonadism. Results: Of all men having TT measurement, 19, 583 (96.4%) were not commenced on TRT (Group A) and 716 (3.5%) men were commenced on TRT (Group B). Men prescribed TRT (Group B) had higher mean age, body mass index (BMI) and higher risks of hypertension, depression type 2 diabetes and ischaemic heart disease; conversely, men in Group B had lower mean pretreatment TT and were less likely to have prostate cancer. Four‐hundred and thirty‐six men (24.3%) with TT < 8 nmol/L and symptoms of low libido were not prescribed TRT. Conclusions: Our study highlights several factors which may influence the decisions made by clinicians when initiating TRT in primary care. Clearer guidance for clinicians may help to improve the consistency of treatment of men with hypogonadism.